Supply Chain and Finance Integration: Facts from Companies in Indonesia - Jatmiko, Bambang; Machmuddah, Zaky; Suhana, Suhana; Laras, Titi (ExcelingTech, 2020)
Abstract— In order to minimize costs and increase productivity, businesses around the world are reforming their supply chains. As they do so, operations are also transferred to countries that levy lower rates of income tax. Recent evidence suggests that some businesses are connecting supply chain decisions with income tax planning in order to create a tax-efficient supply chain aimed at optimizing net revenue. The population in this paper was companies in the city of Semarang, Indonesia. The sampling technique is based on incidental sampling technique. Respondents becoming the sample is 200 respondents. The results of the analysis using the Warp-Partial Least Squares (PLS) 5.0 model indicate that continuity, strategy and finance influence the supply chain and tax planning. The results of the paper also indicate that finance and continuity do not mediate the relation between supply chain and company performance. The implication of the research is that integration perceptions of supply chain and tax planning may be influenced by intrinsic and extrinsic factors of each individual. Therefore, the importance of awareness implanting the moral values of each individual to avoid supply chain and tax planning is urgent. However, it requires the participation of the government through the world of education.